Socio-cultural factors of updating the content of school education - Levshina S. V. (Humanitarian, 2017)
this article examines the phenomenon of socio-cultural conditionality of updating the content of school education in Russia. Socio-cultural factors of updating the content of education have been identified on the basis of theoretical analysis and generalization of scientific and educational research results and evidence of educational practice. The author shows the relationship between selected factors – the development of society, the state policy in the field of education, development of culture and science, development of pedagogical science and practice – and the specificity of their influence on the formation and implementation of the content of school education.
Keywords: школа; содержание образования; общее образование; School; социокультурная обусловленность; социокультурные факторы; the content of education; General education; socio-cultural conditioning; socio-cultural factors